Aplikasi Penunjang Keputusan Pemberian Pinjaman Bergulir PNPM Mandiri Perkotaan Kepada Usaha Kecil dan Menengah (UKM) - Fuad, Hilmi; Nurjanah, Siti (STMIK Bina Sarana Global, 2015)
Along with the development of the modern era, and the rapid advancement of information technology today, the need for a computerized data already covers all fields including in government agencies such as the Office of the village or the village office in Daon village is one of the villages that receive assistance national program community Empowerment (PNPM). This program is one of the efforts to improve the problem of poverty. In the village of Daon current data processing system is already using Microsoft Excel program in the process of inputting the data to the public who will receive a revolving loan national community empowerment program (PNPM). But what happened in the village of Daon is a lot of help Loan Revolving nasioanl community empowerment program (PNPM) self misdirected people who do not have a lot of effort but get this help. Often also occur duplicate data that receive this assistance. to indent the improvement of the system running. Methods of data collection using observation method, the method of literature and interviews, while the design method used in this study was the observation method, interview method, and the method library. In this stage, the authors use the method orinted Object Analysis and Design (OOAD), which includes the analysis and design of a system object approach. And the author uses UML (Unified Modeling Language), which consists of Use Case Diagrams, Sequence Diagrams, Activity diagram, Class diagram, and to design software program author uses PHP and data base SQLYog. With the creation of this system results in a system that gives the decision to administer revolving loan PNPM Mandiri and has no misdirected or PNPM Mandiri revolving loan are multiple.